Analysis of Particulate Matter (PM) Emissions in Diesel Engines Using Palm Oil Biodiesel Blended with Diesel Fuel - Ahmad Fitri, Yusop; R., Mamat; Yusaf, Talal; G., Najafi; Mohd Hafizil, Mat Yasin; Akasyah, M Khathri (MDPI AG, 2018)
This study has focused on the PM emissions of diesel engines. Diesel engines are attractive power units that are used widely in many fields and have become one of the larger contributors of total petroleum consumption. However, diesel engines are among the main contributors of emissions into the air, especially particulate matter (PM) and nitrogen oxides (NOx). PM is one of the major pollutants emitted by diesel engines and has adverse effects on human health. Accordingly, many studies have been conducted to find alternative fuels that are clean and efficient. Biodiesel, which produces less PM than diesel fuel, is preferred as an alternative source for diesel engines. Therefore, using palm oil methyl ester (POME) for diesel engines would be a more economical and sustainable solution. This study has focused on the PM emissions of diesel engines fuelled by a diesel and POME blend (B5, B10, B20, and B100). A comparison between diesel and the POME blend has been made which involves PM mass concentration and its components (soluble organic fraction (SOF) and dry soot (DS)). Combustion characteristics, such as in-cylinder pressure and rate of heat release of the engine, as well as gaseous emissions, have also been observed at different operating engine loads (0.05 MPa 20%, 0.4 MPa 40%, and 0.7 MPa 60%). The results show that PM emissions of B100 are lower than those of diesel fuel owing to the oxygen content of POME.With regard to the SOF concentration, B100 has a higher SOF value than diesel fuel at all engine loads. Meanwhile, the DS for B100 is than that of diesel fuel. Moreover, as the engine load increased, PM and SOF concentrations increased, while DS concentration decreased. The observation of in-cylinder pressure showed that the increment of pressure with the increasing POME blend, as well as the increasing engine load due to the high cetane number for B100, led to a short ignition delay. The engine brake thermal efficiency between the POME blend and mineral diesel was comparable. Furthermore, B100 fuels showed lower engine power at higher brake-specific fuel consumption compared to other tested fuels. In terms of gaseous emissions, increasing POME blends led to an increase in NOx emissions. Meanwhile, as the engine load increased, NOx also continued to increase. The effect of the POME blend on the PM-NOx trade-off observation showed that B100 simultaneously increased the NOx and decreased the PM emissions. It can be concluded that POME creates a lower PM concentration while giving some negative feedback to NOx.